The everything guitar chords book : over 2,000 chords for every style of music - Schonbrun, Marc (Everything series., 2025)
"The Everything Guitar Chords Book, 2nd Edition is your comprehensive guide to mastering guitar chords. This book takes you on a journey from the most basic chords to the most complicated ones featuring clear, easy-to-follow diagrams of each chord as well as links to online audio of 100 essential chords, making it easier than ever for you to practice and perfect your skills. This book covers major, minor, augmented, diminished, and "special" chords, giving you a wide range of options to choose from. It also includes sample chord progressions in every style, helping you understand how different chords work together to create beautiful music. It also offers lessons on the theory of chord construction so you can understand the science behind the music. With thousands of useful and unique chords to choose from, this book is a must-have for musicians of all levels"--